Clinical and neurophysiological features of familial cortical myoclonic tremor with epilepsy. Issue 11 (10th September 2016) - Cen, Zhidong; Huang, Chunping; Yin, Houmin; Ding, Xueping; Xie, Fei; Lu, Xingjiao; Ouyang, Zhiyuan; Lou, Yuting; Qiu, Xia; Wang, Zhongjin; Xiao, Jianfeng; Ding, Meiping; et al.
ABSTRACT: Objective: Familial cortical myoclonic tremor with epilepsy is a rare epilepsy syndrome. Herein, we report on nine Chinese familial cortical myoclonic tremor with epilepsy pedigrees to delineate its clinical and neurophysiological features. Methods: Detailed clinical and neurophysiological data were obtained. Somatosensory evoked potential amplitudes and clinical profile were analyzed using multilevel statistical models. Age‐at‐onset anticipation was analyzed using Kaplan‐Meier survival analysis. Results: Fifty‐five patients were interviewed directly, whose mean age at onset of cortical tremor and generalized tonic‐clonic seizures were 31.0 ± 8.3 and 36.0 ± 7.9 years. Giant somatosensory evoked potential was detected in 87.5% (28 of 32) of patients, and long‐latency cortical reflex was detected in 93.5% (29 of 31). Cortical tremor severity was significantly higher in patients with longer disease duration of cortical tremor ( P = 0.0061). Somatosensory evoked potential amplitudes were significant higher in patients with higher level of cortical tremor severity ( P = 0.0003) and those using antiepileptic drugs ( P = 0.0150). Age‐at‐onset anticipation of cortical tremor with paternal transmission was found with statistical significance ( P = 0.022). Conclusion: We provided the clinical and neurophysiological features of familial cortical myoclonic tremor with epilepsy patients. This study is reported for the presentation of this rare disease in a Chinese population with the largest single report on familial cortical myoclonic tremor with epilepsy worldwide. Age‐at‐onset anticipation of cortical tremor with paternal transmission was statistically significant, which further confirmed a possibility of unstable expanding repeat in the genetic mechanism of familial cortical myoclonic tremor with epilepsy. © 2016 International Parkinson and Movement Disorder Society